Parametric study of added resistance and ship motion in head waves through RANS : Calculation guideline. (May 2021) - Kobayashi, Hiroshi; Kume, Kenichi; Orihara, Hideo; Ikebuchi, Takuro; Aoki, Ichiro; Yoshida, Ryo; Yoshida, Hisafumi; Ryu, Tomohiro; Arai, Yuji; Katagiri, Kosuke; Ikeda, Seiji; Yamanaka, Shota; et al.
Abstract: A comprehensive parametric study concerning added resistance and ship motion in head waves is conducted with an overset approach based on a structured grid system using an in-house Navier-Stokes solver and recommended configurations are proposed as a guideline. The overset approach enables studying wave propagation separately from viscous flow around a hull by omitting the grid for the hull. The parametric study on computing wave propagation of different configurations without a hull in different wavelengths provides recommended domain size, grid resolution and computational conditions such as the time interval. Computations with a hull of Japan bulk carrier (JBC) are conducted to investigate interactions between incident waves and ship motions by using the overset approach. Surge motion can be fixed, and wall function can be applied to the near-wall region. The obtained configuration is applied to a different hull form, the Duisburg Test Case (DTC) and computed results show good agreement with measured data. The achieved configurations are validated and provide a common practice for computing the added resistance and ship motion in head waves by using the flow solver with the described numerical framework.